Effect of Delaminated MXene (Ti3C2) on the Performance of Cement Paste. (28th April 2019) - Zhu, Jianping; Li, Genshen; Feng, Chunhua; Wang, Libo; Zhang, Wenyan
Abstract : Delaminated MXene was incorporated into cement to improve the properties of cement composites, and its effects on the hydration process, microstructures, and mechanical properties were investigated, respectively. The investigation results showed that delaminated MXene was well-dispersed in the cement matrix and significantly reinforced the compressive strength of cement, especially when the addition is 0.01 wt%. Meanwhile, the total hydration heat of cement hydration and the quantity of hydration products were increased with the addition of delaminated MXene. In addition, the formation of HD C-S-H gel was promoted, and the microstructure of hydrated cement became more compact.